Bibliometric study on the application of manganese dioxide in environmental catalysis worldwide from 1991 to 2021. Issue 3 (18th January 2023) - Guo, Yaoguang; Chen, Qianqian; Sun, Xiaohu; Liu, Yujing; Guan, Jie; Zhang, Xiaojiao; Liu, Nuo; Lou, Xiaoyi; Li, Yingshun; Zhang, Xiangwen
Abstract : Structure activity relationship, density functional theory, catalytic oxidation and mechanism have become the frontier in MnO2 environmental catalysis. Abstract : Since the 21st century, manganese dioxide (MnO2 ) has been attracting increasing attention in the environmental and energy fields due to its excellent catalytic oxidation properties. To better grasp the development and trend of MnO2 in the field of environmental catalysis, the published literature studies in the Science Citation Index Expanded database in the Web of Science Core Collection from 1991 to 2021 with a total of 1133 articles and reviews were analyzed by using visualization software of CiteSpace and VOSviewer. The results show an exponential growth in the number of papers related to MnO2 in the environmental catalysis field, with China, USA, India, South Korea and Australia providing the main drivers, while China being the most active country, with Applied Catalysis B-Environmental, Environmental Science & Technology, Catalysis Today and Chemical Engineering Journal being the most important sources for publishing relevant research. At present, a more complete theoretical framework and research methods have been formed for MnO2 environmental catalysis worldwide, but the research network is too centralized and the frontier branches are few. The catalytic research on MnO2 has been expanded from the macroscopic level to the microscopic scale. Structure–activity relationship, density functional theory, catalytic oxidation and mechanism have become the frontier of research. The present study is of significance for better understanding and supporting further research on the MnO2 environmental catalytic process.